Application of computer technologies in teaching art disciplines (Pedagogy of Higher and Secondary Education, 2006)
In the article the questions of application of computer technologies ate considered in teaching of such disciplines of art as an academic picture, academic pamting, decorative-applied art. composition and the articles of designer direction.
Keywords: computer technologies; artistic education; professional knowledges